SISTEM MONITORING KEKERUHAN AIR MENGGUNAKAN SENSOR TURBIDITY DAN TRANCEIVER LORA EBYTE E220 PADA PENYEDIAAN AIR MINUM DAN SANITASI MASYARAKAT (PAMSIMAS) - Jannah, Wardatul; Firmawati, Nini (Jurnal Fisika Unand, 2025)
water turbidity monitoring system has been created using a turbidity sensor and LoRa Ebyte E220 transceiver for the provision of drinking water and community sanitation (PAMSIMAS). The tool designed in this research uses two LoRa Ebyte E220 transceivers, one functions as a transmitter (sender), and the other functions as a receiver (receiver). The sending unit is equipped with a SEN0189 turbidity sensor to detect water turbidity levels, as well as a NodeMCU ESP8266 as a data processor and sender. The receiving unit is equipped with a NodeMCU ESP8266 as a data processor, an LCD to display the results of monitoring turbidity levels, and a buzzer as an alarm that sounds if the water turbidity exceeds a certain threshold. The webserver used is ThingSpeak. The research results show that the system is capable of transmitting water turbidity level data through the air by the Ebyte E220 LoRa transceiver. The SEN0189turbidity sensor system has an average error percentage of 7.6%. This error can be caused by several factors, including the sensor's sensitivity to changes in light intensity, variations in impurity particles in the water, and the sensor's inability to distinguish the types of particles present in the water. LoRa transceivers can transmit data when there is a barrier up to 800 m, while without a barrier it reaches 2000 m. The values obtained from the sensors are displayed on the LCD and ThingSpeak.